El Hierro UNESCO Geopark: Geological Heritage, Geoconservation and Geoturism. - Ramón Casillas Ruiz; Yurena Pérez Candelario; Cristina Ferro Fernández (Geoconservation Research)
El Hierro UNESCO Global Geopark, the first declared in the Canary Islands, treasures an impressive geological heritage, represented by its Geological Interesting Places (GIPs or geosites) has as foremost exponents those related to the formation of mega-landslides and the formation of extensive fields of pahoehoe lava-flows associated with the historical or prehistoric fissure vulcanism that occurred concerning the activity of its three ridges. This interesting geological heritage has been made available to the island's human community, embodied in an incipient geological tourism as a complement and continuity to the sustainable growth policy initiated by the local authorities decades ago.